2000
DOI: 10.1128/aem.66.5.2085-2095.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phenotypic Characterization of Pseudomonas spp. Isolated from Milk

Abstract: Putative Pseudomonas spp. isolated predominantly from raw and processed milk were characterized by automated ribotyping and by biochemical reactions. Isolates were biochemically profiled using the Biolog system and API 20 NE and by determining the production of proteases, lipases, and lecithinases for each isolate. Isolates grouped into five coherent clusters, predominated by the species P. putida (cluster A), P. fluorescens (cluster B), P. fragi (as identified by Biolog) or P. fluorescens (as identified by AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 26 publications
9
99
0
3
Order By: Relevance
“…Many studies have suggested that the phenotypic classification techniques are solely not adequate for identification of Pseudomonas sp., though, overall, the API 20NE was successful in the identification of all the four Pseudomonas strains that had been isolated from fish. That is in agreement with Wiedmann et al [52], who reported that API 20NE resulted in the proper identification of Pseudomonas isolates to the species level.…”
Section: Histopathological Examinationsupporting
confidence: 82%
“…Many studies have suggested that the phenotypic classification techniques are solely not adequate for identification of Pseudomonas sp., though, overall, the API 20NE was successful in the identification of all the four Pseudomonas strains that had been isolated from fish. That is in agreement with Wiedmann et al [52], who reported that API 20NE resulted in the proper identification of Pseudomonas isolates to the species level.…”
Section: Histopathological Examinationsupporting
confidence: 82%
“…Dentre os isolados Gram-negativos (75,2%), 27% e 48% foram, respectivamente, Gram-negativos fermentadores e Gram-negativos não-fermentadores. A predominância do isolamento de bactérias Gram-negativas, observada nas amostras de leite cru refrigerado está de acordo com resultados de outras pesquisas, nas quais elas são consideradas como contaminantes mais freqüentes [11,15] 58%, 58% e 47% possuíam atividade de proteases, lipases e de lecitinase, respectivamente [43].…”
Section: -Isolamento E Caracterização De Bactérias Psicrotróficas Prounclassified
“…Bactérias do gênero Pseudomonas têm sido isoladas com maior freqüência do leite e de produtos lácteos refrigerados [11,13,14,15,43], embora não representem mais do que 10% da microbiota do leite cru recém-ordenhado [35]. Esse gênero inclui espécies que apresentam um tempo de geração curto, entre 0 °C e 7 °C, e uma temperatura mínima de crescimento baixa, de até -10 °C [35].…”
Section: -Introduçãounclassified
“…Hose nozzles and milking equipment can become colonized by Pseudomonas. Also, API 20 NE provided good identification of dairy Pseudomonas isolates to the species level (14,15). In the present study, 15 Pseudomonas strains isolated from raw milk, identified by using API 20 NE and good identification was obtained.…”
Section: Discussionmentioning
confidence: 87%